Sleep complaints in early pregnancy. A cross-sectional study among women attending prenatal care in general practice - Ruth K. Ertmann; Dagny R. Nicolaisdottir; Jakob Kragstrup; Volkert Siersma; Melissa C. Lutterodt (BMC, 2020)
Abstract Background Sleep problems in late pregnancy are common, but sleep in early pregnancy is less well described. The aim of this study was to describe the occurrence and severity of sleep complaints in early pregnancy. We asked the women about worries due to sleep problems. Furthermore, we investigated the associations between sleep complaints and pregnancy-related symptoms. This association was studied taking into account physical and mental health, sociodemographic characteristics, and reproductive history of the women. Methods Cross-sectional study in Danish general practice based on an electronic questionnaire completed by pregnant women and a Pregnancy Health Record filled in by the general practitioner (GP). The questionnaire measured three sleep complaints and 11 common physical pregnancy-related symptoms. The sleep complaints were measured as mild, moderate or severe, and it was recorded how much they worried the women. The associations between the physical pregnancy-related symptoms and sleep complaints were assessed by odds ratios from multivariable logistic regression models. Results The questionnaire was completed by 1338 out of 1508 eligible women before the end of gestation week 16. The gestational age ranged from 5 to 16 weeks (median 11 weeks) among the included women. On average, more than one third of the women reported to have at least one of the three sleep complaints in the questionnaire. Problems "taking a long time to fall asleep" was reported by 312 women (23%), "waking up too early" was reported by 629 (47%), and 183 (14%) had been "lying awake most of the night". One sleep complaint was reported by 38%, two by 16, and 4% had all three symptoms. The majority were not at all or only mildly worried because of their sleep disturbances, but moderate or severe worries were found among 46% of those" taking a long time to fall asleep" and among 40% of those "lying awake most of the night". "Moderate or severe complaints" were reported by 277 (21%) women "Moderate or severe complaints" were associated with pregnancy-related physical symptoms, such as back pain, pelvic girdle pain and pelvic cavity pain, but only the association with pelvic cavity pain stayed significant after adjustment for depression. Conclusion This study showed that sleep complaints in early pregnancy are common, and sleep complaints showed association with physical as well as mental symptoms. It may be important for pregnant patients that clinicians address depression, and mood in relation to sleep problems during pregnancy.